Effects of surfactants on the fractionation, vermiaccumulation, and removal of fluoranthene by earthworms in soil. (July 2020) - Shi, Zhiming; Wang, Congying; Zhao, Yonghua
Abstract: Vermiremediation, which uses earthworms to remediate polluted soils, is an expanding technology in recently years. Surfactants have been widely used in bioremediation and other remediation technologies. However, the roles of surfactants in vermiremediation have been rarely studied. In this paper, an investigation of the effects of Tween-80 and rhamnolipid surfactant on the fluoranthene fraction distribution, vermiaccumulation, and removal during vermiremediation was conducted. Both Tween-80 and rhamnolipid improved the proportion of the desorbed fraction, bound residual fluoranthene, and correspondingly, proportions of the non-desorbed fraction were reduced. The vermiaccumulation of fluoranthene was significantly elevated by 35–64.1% and 34.5–44.2% by the Tween-80 and rhamnolipid, respectively. The vermiaccumulation of fluoranthene is positively correlated with the proportion of desorbed fraction of fluoranthene. Moreover, Tween-80 and rhamnolipid enhanced the removal of fluoranthene from contaminated soil during vermiremediation by 43.6–189.2% and 14.7–45.6%, respectively. The enhanced removal of fluoranthene was attributed to stimulated microbial degradation and increased vermiaccumulation resulting from the desorption ability of surfactants and earthworm activity. However, the total amount of fluoranthene that accumulated in earthworms was approximately 4–10% of the initial amount in the treatments, which suggested that microbial degradation rather than direct uptake contributed to the fluoranthene removal. The study suggests that the use of surfactants to enhance the efficiency of vermiremediation of polycyclic aromatic hydrocarbons (PAHs) contaminated soils might be feasible, and that surfactants-enhanced vermiremediation is an alternative strategies for treat PAHs contaminated soils. Graphical abstract: Image 100816 Highlights: Surfactants altered the speciation of fluoranthene in soil during vermiremediation. Surfactants improved the vermiaccumulation of fluoranthene by earthworms in soil. Surfactants enhanced the removal of fluoranthene from soil during vermiremediation. Microbial degradation is the key cause of the removal of PAHs during vermiremediation.